Impact of Ureaplasma urealyticum infection on semen parameters and in vitro fertilization outcomes in infertile men - Wan, Yangyang; Chen, Xin; Chen, Zhaoyu; Liu, Wenjing; Li, Siyao; Hua, Juan (Frontiers in Endocrinology, 2024)
Ureaplasma urealyticum (UU) is one of the most prevalent pathogens associated with genital tract infections in infertile males. However, the impact of male UU infection on semen parameters and in vitro fertilization (IVF) outcomes remains insufficiently explored. This study retrospectively analyzed 1,215 infertile couples at the First Hospital of USTC. Participants were categorized into two groups based on the male partner's infection status: UU-positive (n=249) and UU-negative (n=966). The objective was to evaluate the effect of male UU infection on semen quality, embryo development, pregnancy outcomes, and neonatal health. The findings revealed that semen parameters such as sperm concentration, motility, and morphology were largely similar between the two groups. However, the UU-positive group had significantly elevated levels of anti-sperm antibodies (ASA) (p=0.020) and high DNA stainability (HDS) (p=0.014). Despite these differences in semen quality, embryo quality measures, including the fertilization rate and blastocyst formation rate, were not significantly affected by UU infection. Pregnancy outcomes, including clinical pregnancy and live birth rates, were also comparable between the groups. Although the UU-positive group experienced a slightly higher miscarriage rate, this difference was not statistically significant. Neonatal outcomes, such as gestational age, birth weight, Apgar scores, and preterm delivery rate, were similarly unaffected by UU status. The results indicate that UU infection in infertile males may negatively impact semen parameters; however, its influence on reproductive and neonatal outcomes appears limited within the context of IVF.Therefore, IVF remains a viable and safe option for infertile couples with male UU infection.